1999
DOI: 10.1542/peds.104.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Natural Outcome ofHelicobacter pyloriInfection in Asymptomatic Children: A Two-year Follow-up Study

Abstract: These findings demonstrate a deterioration in the histologic features of the gastric mucosa of infected children despite stable H pylori colonization and the absence of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 32 publications
1
33
0
4
Order By: Relevance
“…On the other hand, the bacterial dose of H. pylori might not be sufficient and thus, might not survive well in the harsh environment of the stomach. Inability of H. pylori to survive in young children can be speculated from reports that seropositive younger children often show seroreversion to seronegative when they grow older (8,10,14,15,17). On the other hand, there is a report that finds no seroconversion in children (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the bacterial dose of H. pylori might not be sufficient and thus, might not survive well in the harsh environment of the stomach. Inability of H. pylori to survive in young children can be speculated from reports that seropositive younger children often show seroreversion to seronegative when they grow older (8,10,14,15,17). On the other hand, there is a report that finds no seroconversion in children (24).…”
Section: Discussionmentioning
confidence: 99%
“…It is now suggested that the infection occurs mostly during the younger age and that there are cohort effects (15,(23)(24)(25). These surveys were carried out using seroconversion as the marker for infection (6,8,10,13,14). Seroconversion only suggests that a child has encountered a sufficient dose of H. pylori to induce seroconversion, but does not necessarily have a current infection.…”
mentioning
confidence: 99%
“…Nodular gastritis, a pathognomonic endoscopic fi nding in H. pylori -infected children, indicates a high grade of H. pylori colonization and chronic active gastritis with lymphoid follicles with germinal center or MALT, exaggerated by infl ammatory reaction caused by H. pylori infection [ 10 , 11 ], and its severity may deteriorate as time passes [ 12 ]. In previous studies, antral nodularity in children were correlated with higher histological scores on the gastric mucosa, indicating higher severity of gastritis, and was also associated with higher density of H. pylori and cagApositive strains [ 13 , 14 ].…”
Section: Histopathologic Findings In H Pylori -Infected Childrenmentioning
confidence: 99%
“…There are indirect evidences to suggest that resolution of inflammatory response may occur more rapidly in children than had been reported for adults [23]. In France, Ganga-Zandzou and colleagues prospectively monitored the consequences of untreated H. pylori infection in a group of asymptomatic children [24]. Although the density of bacterial colonization was not changed, there was both marked antral nodularity and more severe mucosal inflammation in the antrum over the 2-year follow-up of the children.…”
Section: Consequences Of Initial H Pylori Infection In Childrenmentioning
confidence: 99%